The Principal's Role in Improving Teacher Performance in SMP Negeri 3 Way Bungur, East Lampung Regency - Eka Sulistiyowati; Dewi Indriati Daulay; Nova Putriana Daulay; Ade Suherman; Andi Warisno (CV. Tripe Konsultan, 2022)
The purpose of this study was to reveal the principal's role in improving the teachers' performance of SMP Negeri 3 Way Bungur, East Lampung Regency. This study uses a descriptive-analytic method with a qualitative approach. This research was conducted at SMP Negeri 3 Way Bungur, East Lampung. The research subjects were the Principal and Teachers of SMP Negeri 3 Way Bungur. This data collection technique was obtained from observations, interviews and summary of field notes. The analytical techniques used in this study are: (1) data collection, (2) data reduction, (3) data presentation, (4) and drawing conclusions. The results showed that there are 7 roles of principals in improving teacher performance including, 1) principals as educators; 2) the principal as manager; 3) The role of the principal as administrator; 4) The role of the principal as a supervisor; 5) The role of the principal as a leader; 6) The role of the principal as a motivator; and 7) The role of the principal as an innovator.